The Cesáro Core of Double Sequences - Kuddusi Kayaduman; Celal Çakan (Abstract and Applied Analysis)
We have characterized a new type of core for double sequences, 𝑃𝐶-core, and determined the necessary and sufficient conditions on a four-dimensional matrix 𝐴 to yield 𝑃𝐶-core𝐴𝑥⊆𝛼(𝑃-core𝑥) for all ℓ∞2.